Secular Changes in U.S. Prediabetes Prevalence Defined by Hemoglobin A(1c) and Fasting Plasma Glucose: National Health and Nutrition Examination Surveys, 1999–2010 - Bullard, Kai McKeever (American Diabetes Association, 2013)
OBJECTIVE: Using a nationally representative sample of the civilian noninstitutionalized U.S. population, we estimated prediabetes prevalence and its changes during 1999–2010. RESEARCH DESIGN AND METHODS: Data were from 19,182 nonpregnant individuals aged ≥12 years who participated in the 1999–2010 National Health and Nutrition Examination Surveys. We defined prediabetes as hemoglobin A(1c) (A1C) 5.7 to <6.5% (39 to <48 mmol/mol, A1C5.7) or fasting plasma glucose (FPG) 100 to <126 mg/dL (impaired fasting glucose [IFG]). We estimated the prevalence of prediabetes, A1C5.7, and IFG for 1999–2002, 2003–2006, and 2007–2010. We calculated estimates age-standardized to the 2000 U.S. census population and used logistic regression to compute estimates adjusted for age, sex, race/ethnicity, poverty-to-income ratio, and BMI. Participants with self-reported diabetes, A1C ≥6.5% (≥48 mmol/mol), or FPG ≥126 mg/dL were included. RESULTS: Among those aged ≥12 years, age-adjusted prediabetes prevalence increased from 27.4% (95% CI 25.1–29.7) in 1999–2002 to 34.1% (32.5–35.8) in 2007–2010. Among adults aged ≥18 years, the prevalence increased from 29.2% (26.8–31.8) to 36.2% (34.5–38.0). As single measures among individuals aged ≥12 years, A1C5.7 prevalence increased from 9.5% (8.4–10.8) to 17.8% (16.6–19.0), a relative increase of 87%, whereas IFG remained stable. These prevalence changes were similar among the total population, across subgroups, and after controlling for covariates. CONCLUSIONS: During 1999–2010, U.S. prediabetes prevalence increased because of increases in A1C5.7. Continuous monitoring of prediabetes is needed to identify, quantify, and characterize the population of high-risk individuals targeted for ongoing diabetes primary prevention efforts.